Evaluation of a Problem Based Learning Curriculum Using Content Analysis - Titi Savitri Prihatiningsih; Nurul Qomariyah (International Journal of Evaluation and Research in Education (IJERE), 2016)
Faculty of Medicine UGM has implemented Problem Based Learning (PBL) since 1985. Seven jump tutorial discussions are applied. A scenario is used as a trigger to stimulate students to identify learning objectives (LOs) in step five which are used as the basis for self study in step six. For each scenario, the Block Team formulates the LOs which are informed to tutors. Tutors have to facilitate the discussion that the correct LOs are identified. This study checked the allignment of LOs formulated by the Faculty and LOs by the students. Cardiorespiratory system block is used. A content analysis is applied for this purpose. Sixteen discussion notes (DNs) written by 16 groups from one scenarios were analysed. The LOs from the tutor book and DNs were coded separately. There were eight Faculty LOs for scenario Blood Donation. None DNs were mentioned correctly. Many DNs mentioned LOs which are not in the prescribed LOs. It was clear that 16 groups of student failed to identify LOs correctly. This might affect their performance in their block exams, and also their preparedness for the subsequent blocks as they lack relevant prior knowledge.